2001
DOI: 10.1177/107602960100700411
|View full text |Cite
|
Sign up to set email alerts
|

Hemophilia A, von Willebrand Disease, and Atherosclerosis of Abdominal Aorta and Leg Arteries: Factor VIII and von Willebrand Factor Defects Appear to Protect Abdominal Aorta and Leg Arteries From Atherosclerosis

Abstract: We hypothesized that patients with hemophilia or von Willebrand disease might be protected from atherosclerosis because of their coagulation defect. We studied 40 subjects affected by these two coagulation diseases using echocolor Doppler of the abdominal aorta and leg arteries, and compared the results with those obtained in 40 control patients who were homogenous with study patients in terms of sex, age, and risk factors for atherosclerosis. The probands presented a lower number of plaques than the 40 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 13 publications
4
41
0
Order By: Relevance
“…[17][18][19][20][21] Srámek et al 21 and Sartori et al 20 found no differences in IMT, whereas 3 other studies [17][18][19] did show a lower IMT, fewer atherosclerotic plaques, or both in hemophilia patients. In these studies, patients were relatively young; mean age ranged from 40 to 58 years.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…[17][18][19][20][21] Srámek et al 21 and Sartori et al 20 found no differences in IMT, whereas 3 other studies [17][18][19] did show a lower IMT, fewer atherosclerotic plaques, or both in hemophilia patients. In these studies, patients were relatively young; mean age ranged from 40 to 58 years.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, comparison groups were not well chosen and, in some, not well described. [17][18][19][20][21] In addition, confounding was not accounted for in the analyses. These factors make interpretation of the results difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This explains why shear stress cannot explain atherosclerosis resistance in Down's Syndrome [576,577], hemophilia, von Willebrand coagulopathy [578], and patients treated with anticoagulants.…”
Section: Inflammation and Atherosclerosismentioning
confidence: 99%